Why do they kill?: men who murder their intimate partners - Adams, David (Vanderbilt University Press, 2007)
Men who kill their partners -- Recognizing abusive men -- Killer profiles -- The killers' upbringings -- Short courtships -- Child abuse -- Patterns of possession and punishment -- Victim help-seeking -- Conclusions and recommendations